Toward a clinical application of ex situ boron neutron capture therapy for lung tumors at the RA-3 reactor in Argentina - Farías, Rubén Oscar; Garabalino, Marcela Alejandra; Ferraris, Sergio; Santa María, Juan; Rovati, Osvaldo Daniel; Lange, Fernando; Trivillin, Verónica Andrea; Monti Hughes, Andrea; Pozzi, Emiliano César Cayetano; Thorp, Silvia Inés; Curotto, Paula; Boltolussi, S.; et al. (Wiley, 2015)
Fil: Farías, Rubén Oscar. Comisión Nacional de Energía Atómica. Gerencia de Area de Aplicaciones de la Tecnología Nuclear. Gerencia de Radiobiología (Centro Atómico Constituyentes); Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina